MENA Economies Hit by Conflicts, Civil Wars, and Lower Oil Prices - Mottaghi, Lili (World Bank, Washington, DC, 2015)
Against the backdrop of a slowing global economy and lower commodity prices, economic growth in the Middle East and North Africa (MENA) is stagnating. The World Bank 2015 MENA economic monitor report projects overall gross domestic product (GDP) growth to be less than 3 percent for the third year running - about 2.8 percent for 2015. Low oil prices, conflicts, and the global economic slowdown make short-term prospects of recovery unlikely. In a positive scenario of decreasing tensions in Libya, Iraq, and Syria, together with recovery in the Euro area that can boost external demand, growth in the region can rebound to 4.4 percent in 2016 and the following year. However, if current circumstances persist, overall growth is not expected to recover any time soon. Since the 2011 Arab spring, though not necessarily because of it, the MENA region has seen a slowdown in economic growth, an escalation of violence and civil war and, more recently, substantial macroeconomic imbalances from lower oil prices.